2019
DOI: 10.3390/ijms20030699
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL Related to ROS Formation under Hypoxia and Their Association with Waterlogging and Salt Tolerance in Barley

Abstract: Waterlogging is a serious environmental problem that limits agricultural production in low-lying rainfed areas around the world. The major constraint that plants face in a waterlogging situation is the reduced oxygen availability. Accordingly, all previous efforts of plant breeders focused on traits providing adequate supply of oxygen to roots under waterlogging conditions, such as enhanced aerenchyma formation or reduced radial oxygen loss. However, reduced oxygen concentration in waterlogged soils also leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 89 publications
(105 reference statements)
2
32
1
Order By: Relevance
“…All of these suggest that there might not be a clear, general correlation between waterlogging stress tolerance and the activity of major enzymatic antioxidants, but a more genotype-dependent one. When performing GO enrichment analysis on up and down-regulated genes, ROS related GO terms were down-regulated in Deder2 at 72 and 120 h. For example, the discrepancy between our results and those reported by Gill et al [33] that screened the barley roots for ROS production under hypoxia stress could be due to the treatment applied (hypoxia solution-0.2% agar vs. waterlogging) but most likely is due to the timing of the measurements, 48 h vs. 72 and 120 h. Previously, Zhu et al [69] has shown that the activities of SOD, CAT, and POD in grapevine leaves under waterlogging stress increased substantially compared to the control but began declining after 24 h (CAT) and 96 h (SOD and POD). A similar trend was observed in Deder2 for those three POD up-regulated genes identified in our study where they were more expressed at 72 h (2.56, 2.00, and 2.21 logFC) compared to 120 h (2.15, 1.48, and 1.47 logFC).…”
Section: Effects On Ros Productioncontrasting
confidence: 99%
See 2 more Smart Citations
“…All of these suggest that there might not be a clear, general correlation between waterlogging stress tolerance and the activity of major enzymatic antioxidants, but a more genotype-dependent one. When performing GO enrichment analysis on up and down-regulated genes, ROS related GO terms were down-regulated in Deder2 at 72 and 120 h. For example, the discrepancy between our results and those reported by Gill et al [33] that screened the barley roots for ROS production under hypoxia stress could be due to the treatment applied (hypoxia solution-0.2% agar vs. waterlogging) but most likely is due to the timing of the measurements, 48 h vs. 72 and 120 h. Previously, Zhu et al [69] has shown that the activities of SOD, CAT, and POD in grapevine leaves under waterlogging stress increased substantially compared to the control but began declining after 24 h (CAT) and 96 h (SOD and POD). A similar trend was observed in Deder2 for those three POD up-regulated genes identified in our study where they were more expressed at 72 h (2.56, 2.00, and 2.21 logFC) compared to 120 h (2.15, 1.48, and 1.47 logFC).…”
Section: Effects On Ros Productioncontrasting
confidence: 99%
“…ROS-scavenging enzymes and antioxidants are induced to protect the plants against ROS, which is accumulated under waterlogging conditions creating oxidative stress [60]. They play a critical role, in the plant cells, in the survival under waterlogging of many plants, such as winter wheat [61], maize [45], barley [33], and cucumber [62]. The top 11 Biological Process GO terms for all DEGs were related to ROS catabolic processes, including hydrogen peroxide metabolic process, detoxification, oxidation-reduction process, response to oxidative stress, etc.…”
Section: Effects On Ros Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another pathway through which contemporary models could account for effects of waterlogging is oxidative stress damage. This is because exposure of plants to hypoxia or anoxia conditions causes oxidative stress, which affects plant growth due to the production of superoxide radicals, hydroxyl radicals, and hydrogen peroxide (Gill et al, 2019; Mittler et al, 2004). ROS accumulation also results in a significant disturbance to plant ionic homeostasis, directly affecting activity of various cation (Gill et al, 2019; Shabala et al, 2014) and anion channels (Pottosin et al, 2018).…”
Section: Plant Physiological Processes That Should Inform Future Modementioning
confidence: 99%
“…Plants minimize oxidative stress by producing enzymatic and nonenzymatic antioxidants. The antioxidant enzyme system, such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), alleviate and scavenge waterlogging-induced ROS production from the plant cells (Gill et al 2019, Jia et al 2019, Wang et al 2019b. SOD catalyzes the conversion of O2 •into O2 and H2O2, while H2O2 is effectively scavenged by POD and CAT.…”
Section: Introductionmentioning
confidence: 99%